ISLAMIC MORAL VALUES ACCORDING TO BUYA HAMKA: IMPLICATIONS FOR CONTEMPORARY ISLAMIC EDUCATION - Satra, Alihan; Romeinita, Elfira; Hidayah, Refiana Ayu Nurul; Rebagus, Handi (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study explores the concept of Islamic moral values as articulated by Haji Abdul Malik Karim Amrullah, widely known as Buya Hamka—a prominent Indonesian Muslim scholar, cleric, and intellectual. In his thought, morality (akhlak) occupies a central role in Islamic education, with the ultimate aim of developing individuals who are not only intellectually competent but also spiritually and ethically grounded. Amid the current moral decline among the younger generation, revisiting Buya Hamka’s ethical framework provides significant insight into how Islamic values can address contemporary challenges. The study employs a qualitative library research method, collecting, analyzing, and interpreting data from Hamka’s primary works—such as Tafsir Al-Azhar, Lembaga Hidup, and Pribadi—as well as secondary sources including scholarly articles and conceptual literature. The findings reveal that Buya Hamka’s moral philosophy is built upon four foundational virtues: hikmah (wisdom), syaja’ah (courage), iffah (self-restraint), and ‘adalah (justice). These principles serve as a moral compass for shaping character, behavior, and educational approaches in both personal and societal contexts. The study also identifies effective methods of moral development proposed by Hamka, such as understanding, habituation, exemplary conduct, advice, storytelling, rewards, and attentiveness—with exemplary conduct being emphasized as the most effective strategy. The research concludes that Buya Hamka’s moral thought offers a comprehensive and timeless model for character education, rooted in the integration of knowledge (‘ilm), faith (iman), and moral action (akhlak), and remains highly relevant for contemporary Islamic educational practices. Penelitian ini mengkaji konsep nilai-nilai moral Islam sebagaimana dikemukakan oleh Haji Abdul Malik Karim Amrullah, yang lebih dikenal sebagai Buya Hamka—seorang ulama, cendekiawan, dan intelektual Muslim terkemuka di Indonesia. Dalam pemikirannya, akhlak menempati posisi sentral dalam pendidikan Islam, dengan tujuan akhir membentuk individu yang tidak hanya cerdas secara intelektual, tetapi juga matang secara spiritual dan moral. Di tengah kemerosotan moral generasi muda saat ini, pemikiran etis Buya Hamka menjadi sangat relevan untuk memberikan solusi berbasis nilai-nilai Islam. Penelitian ini menggunakan metode studi pustaka kualitatif dengan menghimpun, menganalisis, dan menginterpretasikan data dari karya-karya utama Buya Hamka—seperti Tafsir Al-Azhar, Lembaga Hidup, dan Pribadi—serta didukung oleh literatur sekunder seperti artikel ilmiah dan karya konseptual. Hasil penelitian menunjukkan bahwa fondasi pemikiran moral Buya Hamka bertumpu pada empat nilai utama: hikmah (kebijaksanaan), syaja’ah (keberanian), iffah (pengendalian diri), dan ‘adalah (keadilan). Nilai-nilai ini menjadi kompas moral dalam membentuk karakter, perilaku, dan pendekatan pendidikan dalam konteks individu maupun sosial. Studi ini juga mengidentifikasi berbagai metode pembinaan akhlak yang dikemukakan oleh Hamka, seperti pemahaman, pembiasaan, keteladanan, nasihat, cerita, ganjaran (tsawab), dan perhatian—dengan keteladanan sebagai metode paling efektif. Penelitian ini menyimpulkan bahwa konsep moralitas Buya Hamka menawarkan model pendidikan karakter yang komprehensif dan tak lekang oleh waktu, yang mengintegrasikan ilmu, iman, dan akhlak, serta sangat relevan bagi praktik pendidikan Islam kontemporer.